2018
DOI: 10.1126/scisignal.aaq1075
|View full text |Cite
|
Sign up to set email alerts
|

Biased agonists of the chemokine receptor CXCR3 differentially control chemotaxis and inflammation

Abstract: The chemokine receptor CXCR3 plays a central role in inflammation by mediating effector/memory T cell migration in various diseases; however, drugs targeting CXCR3 and other chemokine receptors are largely ineffective in treating inflammation. Chemokines, the endogenous peptide ligands of chemokine receptors, can exhibit so-called biased agonism by selectively activating either G protein–mediated or β-arrestin–mediated signaling after receptor binding. Biased agonists might be used as more targeted therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 70 publications
8
47
0
Order By: Relevance
“…Similarly, the two synthetic compounds, VUF10661 and VUF11418 demonstrated greater cAMP inhibition with reduced βarrestin recruitment. In our analyses, VUF11418 appeared to be G protein biased relative to VUF10661, consistent with prior findings using different methods (24), but with additional nuances of additional signaling pathway potency and efficacy now appreciated. Further analyses showed that CXCL11 is Gαi:β-arrestin biased relative to cAMP inhibition compared to the two small molecules.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similarly, the two synthetic compounds, VUF10661 and VUF11418 demonstrated greater cAMP inhibition with reduced βarrestin recruitment. In our analyses, VUF11418 appeared to be G protein biased relative to VUF10661, consistent with prior findings using different methods (24), but with additional nuances of additional signaling pathway potency and efficacy now appreciated. Further analyses showed that CXCL11 is Gαi:β-arrestin biased relative to cAMP inhibition compared to the two small molecules.…”
Section: Discussionsupporting
confidence: 89%
“…VUF10661's signaling characteristics were extremely different from that of the two pairings. Notably, VUF10661 and VUF11418 are known to differentially regulate chemotaxis and inflammation, consistent with these signaling pathways being physiologically relevant (24). Overall, these findings illuminate signaling granularity within the activity of CXCR3 agonists.…”
Section: Discussionsupporting
confidence: 60%
“…HEK293T cells seeded in 6-well plates were co-transfected with 500 ng of smBiT tagged β-arrestin-2, and either 250 ng of LgBiT tagged receptor or 2000 ng of untagged receptor and varying concentrations of LgBiT G α protein expression vector (most experiments were conducted between 50-200 ng of G α plasmid) or 2000ng of mKO tagged β-arrestin-2 and 500 ng of smBiT tagged V 2 R using a calcium phosphate protocol previously described 28 . Twenty-four hours post-transfection, cells were plated onto clear bottom, white-walled 96-well plates at 50,000-100,000 cells/well in “BRET media” - clear minimum essential medium (GIBCO) supplemented with 2% FBS, 10 mM HEPES, 1x GlutaMax, and 1x Anti-Anti (GIBCO).…”
Section: Methodsmentioning
confidence: 99%
“…Experiments were conducted as previously described 28 . Briefly, cells were serum starved for at least four hours, stimulated with the indicated ligand, subsequently washed 1x with ice-cold PBS, lysed in ice-cold RIPA buffer containing phosphatase and protease inhibitors (Phos-STOP (Roche), cOmplete EDTA free (Sigma)) and rotated for forty-five minutes, and cleared of insoluble debris by centrifugation at >12,000 x g (4 °C, 15 minutes), after which the supernatant was collected.…”
Section: Methodsmentioning
confidence: 99%
“…However, inhibition of MEK/ERK (U0126 or PD98059) does not prevent CXCL11-mediated chemotaxis, whereas PLC inhibition (U73122), PI3K (wortmannin) or, to a lesser extent, AKT inhibition (LY294002) does abrogate or reduce human T cell migration, respectively. Akt activation in human T cells was recently reported to be dependent upon β-arrestin2 14 .…”
Section: Cxcr3 Signaling Pathways In Leukocytesmentioning
confidence: 99%